Drugs acting on the heart: antihypertensive drugs. Issue 5 (May 2015) - Charlton, Matthew; Thompson, Jonathan P.
Abstract Antihypertensive drugs are used commonly in anaesthesia and intensive care medicine. Patients might require antihypertensive drugs before surgery for the treatment of essential hypertension, pre-eclampsia or, occasionally, for conditions such as phaeochromocytoma; during surgery as part of a deliberate hypotensive anaesthetic technique; or to reduce postoperative cardiovascular complications. Here, we discuss the physiology of blood pressure control, the pharmacology of antihypertensive drugs, current guidelines, and practical applications of antihypertensive therapy.